The plight of a plover: Viability of an important snowy plover population with flexible brood care in Mexico. (May 2017) - Cruz-López, Medardo; Eberhart-Phillips, Luke J.; Fernández, Guillermo; Beamonte-Barrientos, René; Székely, Tamás; Serrano-Meneses, Martín A.; Küpper, Clemens
Abstract: Shorebird populations often rely on wetland habitats, for which they are considered important indicators of ecosystem health. Populations residing at low latitudes remain vastly understudied in comparison with populations from high latitudes. Here we use detailed behavioural and demographic observations during all life stages in combination with stage specific modelling to predict the population trajectory of a snowy plover ( Charadrius nivosus ) population at Bahía de Ceuta, Sinaloa, Mexico. In North America this shorebird is threatened, with many monitored populations declining. Our stochastic matrix model for the Ceuta population, which closely matched our field observations, suggests that the population is a sink with a 99.8% probability of going extinct within 25 years. Low apparent adult survival, which declined over time presumably because of poor reproductive success and/or permanent emigration in response to habitat degradation, had the largest impact on the population trajectory. We recommend urgent habitat management actions to address volatile water levels and hence increase reproductive success of this species at this important breeding site. Acknowledging the relative effects of flexible brood care on individual fitness and population dynamics presents an intriguing dilemma for conservation. We found that the flexible parental care system of snowy plovers affected chick survival: broods deserted by polyandrous females early after hatching had significantly lower survival than broods not deserted or those deserted late. Overall, deserting females raised fewer fledglings in this population than females that cared. Taken together, our study reveals unsustainable variation in local vital rate dynamics. To understand how this population contributes to regional source-sink dynamics, future research should evaluate the importance of immigration and emigration among neighbouring populations. Highlights: We evaluated the viability of a subtropical population of the endangered snowy plover. The population viability model suggested a 99.8% probability of extinction within the next 25 years. Brood desertion by polyandrous females contributed to observed low chick survival. Urgent conservation actions are needed to prevent extinction of this regionally important population.